Cladocera (Crustacea, Branchiopoda) of a temporary shallow pond from northern Colombia - Fuentes Reinés, Juan M. (2019)
Eighteen species of cladocerans are recorded from a temporary pond in northern Colombia; 12 of these records are new for La Guajira Department: Diaphanosoma brevireme Sars, 1901, D. dentatum Herbst, 1968, Sarsilotona serricauda (Sars, 1901), Moina micrura micrura Kurz, 1874, M. reticulata Daday, 1905, Grimaldina freyi Neretina and Kotov, 2017, Kurzia polyspina Hudec, 2000, Leydigia cf striata Birabén, 1939, Ovalona cf glabra (Sars, 1905), Chydorus nitidulus (Sars, 1901), Dunhevedia crassa King, 1853 and Pseudosida sp.; this latter taxon could be an yet undescribed species. The cladoceran fauna from the surveyed area is represented mostly by widespread species and commonly found in the Neotropical regions, but local morphological data are scarce in the regional literature. Brief diagnostic descriptions of the species recorded for the Colombian cladoceran fauna are provided together with illustrations of taxonomically significant appendages, morphological remarks, notes on the variability of some species, and their distribution.